NURSING GRAND ROUNDS (NGRS) AND CONTINUING PROFESSIONAL DEVELOPMENT (CPD) OF NURSES - Nuryani, Siluh Nyoman Alit; Wati, Ni Made Nopita; Juanamasta, I Gede; Lestari, Made Pande Lilik; Aungsuroch, Yupin (International Journal of Psychosocial Rehabilitation, 2020)
Continuing Proffesional Development (CPD) enable nurses to continuesly updated their knowledge and skill relevan with current evidende based, it also provide an opportunity for nurses to promote their professionalism and eventually improve patient outcome. The aim of this study was to identify relationship of NGR and CPD among nurses. This study used non-experimental study a cross sectional design , 208 nurses was selected using purposive sampling. Inclusion criteria was nurses had attended NGR previously. Results of this study majority of the respondent were female 81.7% (n=170) and male 18.2 % (n=38). Educational background majority Diploma (DIII) Nursing with 60.1% (n=125), Bachelor Degree of Nursing 31.3 % (n= 65). Majority of nurses have their clinical experience 1-10 years 44%. Nurses who participated majority were medical competency with 33.7 % and surgical competency 29.3 %. Nursing Grand Round results were effective 70.2 % Nurse’s perceived continuing professional development is good (63%) Data also showed in 2017 nurses who were able to achieve CPD requirement 20 hours per years 72.1 % (n=150) and in 2018 increased to 74% (n=154). Bivariate analysis showed there were significant correlation between NGR and perceive of CPD with p value = 0.000 (p<0.05). Therefore, it is recommended to conduct NGR regularly to enhance CPD achievement and quality and safety of nursing care.